Despossessão e escrevivência - Geniane Ferreira; Antonio Rafael Marchezan Ferreira; Rosely Gomes (Revista de Ciências Jurídicas UEM, 2025)
Forced removal in urban areas results in the permanent or temporary dispossession of individuals, families, and communities from their homes or land, violating their rights without providing adequate solutions or appropriate resettlement strategies. This paper investigates the non-material damages caused by this practice, in dialogue with theoretical frameworks and with Conceição Evaristo’s revealing Escrevivência in her novel Becos da Memória (2006). The creative strategy of Escrevivência and Evaristo’s work constitute the corpus and part of the method of the study, transposing into writing the orality and memory of Black women, and revealing socio-spatial exclusion, territorial informality, and tenure insecurity in the outskirts of Brazilian cities. The study also draws on the theoretical contributions of Brah (2005), Anderson (2008), and Hall (2006) on community, boundaries, and belonging. The results highlight the power of Evaristo’s writing, whose fiction/truth unveils psychic suffering, the loss of identity-bearing spaces and accumulated experiences, affecting the sense of belonging and bringing to light rights that have been rendered invisible.